Psicoterapia ontopsicológica: a formação do ontoterapeuta - Accorsi, Ângelo (2019)
The contemporaneity has put everyone in face of the challenge of reviewing and reinventing the way we live and live on this planet. The focus of this study is thinking about psychotherapy formation. Specifically addresses the formation of ontotherapists. Thus, the general objective is to characterize the formation journey in Ontotherapy based on the analysis of the historical formative process of ontotherapists and the formation proposal by Meneghetti. In this way, it was systematized how Meneghetti developed the formation of ontotherapists in Italy and Brazil; a historical biographical survey was conducted about the formation of the active onotherapists in Brazil and also it was evidenced pathways of the formation of new ontotherapists for the exercise of the activity in Brazil. The relevance of studies that are dedicated to discussing and reflecting on the formation of psychotherapist in the contemporary world is in several aspects. Among them is the novelty of the study perspective, as well as the lack of schools for the formation of new ontotherapists nowadays or an institutionally delineated formative course. The present study has a qualitative and interpretative approach. Regarding the participants, a survey was conducted about ontherapists working in Brazil and abroad. Nine ontherapists participated in the study, out of which six are Brazilian and three are Italian data on acting national and international ontotherapists was collected. The research with the participants was performed through a semi-structured interview. In order to fulfill the objectives of the study, it was also carried out a documentary and bibliographical research related to the activities undertaken by Antonio Meneghetti on the formation of ontotherapists. The analysis of the information allowed to obtain results that characterize the formation journey in Ontoterapia. The systematization of the training completed by Meneghetti in Brazil and Italy have demonstrated a consistent structured and documented formation journey that includes theoretical studies, individual psychotherapy, and supervision. It was found that Meneghetti for the formation of ontotherapists also contemplated the realization of residences, congresses, and international events. The analysis of the historical biographical survey of active Brazilian ontherapists indicated to the relevance of the elements: meeting and initial formation with Alécio Vidor and later with Professor Meneghetti and the institutional practice. Pathways of the formation were also evidenced new ontotherapists, whose results highlighted the theoretical and technical principles for the formation; the essential competences and the relevance of the lifestyle, the continuous personal growth, and the continuous formation. The study characterizing the training course in Ontotherapy, evidenced the complexity of this formation; the importance of it for the continuity of the ontopsychological proposal and the inherent challenges related to the fact that there are no schools for the specific training in Ontotherapy. The research recovers of social relevance, focusing on the formation of new generations of ontotherapists and to the continuity of this clinical practice. (The present study was conducted with the support of the National Council of Scientific and Technological Development – CNPq)